General anesthetics have differential inhibitory effects on gap junction channels and hemichannels in astrocytes and neurons. Issue 4 (15th December 2015) - Liu, Xinhe; Gangoso, Ester; Yi, Chenju; Jeanson, Tiffany; Kandelman, Stanislas; Mantz, Jean; Giaume, Christian
Abstract : Astrocytes represent a major non‐neuronal cell population actively involved in brain functions and pathologies. They express a large amount of gap junction proteins that allow communication between adjacent glial cells and the formation of glial networks. In addition, these membrane proteins can also operate as hemichannels, through which "gliotransmitters" are released, and thus contribute to neuroglial interaction. There are now reports demonstrating that alterations of astroglial gap junction communication and/or hemichannel activity impact neuronal and synaptic activity. Two decades ago we reported that several general anesthetics inhibited gap junctions in primary cultures of astrocytes (Mantz et al., (1993) Anesthesiology 78(5):892‐901). As there are increasing studies investigating neuroglial interactions in anesthetized mice, we here updated this previous study by employing acute cortical slices and by characterizing the effects of general anesthetics on both astroglial gap junctions and hemichannels. As hemichannel activity is not detected in cortical astrocytes under basal conditions, we treated acute slices with the endotoxin LPS or proinflammatory cytokines to induce hemichannel activity in astrocytes, which in turn activated neuronal hemichannels. We studied two extensively used anesthetics, propofol and ketamine, and the more recently developed dexmedetomidine. We report that these drugs have differential inhibitory effects on gap junctional communication and hemichannel activity in astrocytes when used in their respective, clinically relevant concentrations, and that dexmedetomidine appears to be the least effective on both channel functions. In addition, the three anesthetics have similar effects on neuronal hemichannels. Altogether, our observations may contribute to optimizing the selection of anesthetics for in vivo animal studies. GLIA 2016;64:524–536 Main points: Three general anesthetics inhibit gap junctions and hemichannels activated by LPS or cytokines in cortical astrocytes. The cytokines also activate hemichannels in cortical neurons, which are similarly inhibited by the anesthetics.